PENGARUH KEGIATAN TARI ANAK KONTEMPORER TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK SANDHY PUTRA - Ines Manalu; Kamtini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of contemporary children's dance activities on the gross motor skills of children aged 5–6 years at Sandhy Putra Kindergarten. This study was motivated by the low development of children's gross motor skills, especially in locomotor skills such as running, jumping, and maintaining body balance. This study used a quantitative approach with a quasi-experimental method through a nonequivalent control group design. The study population was 44 children aged 5–6 years, while the study sample consisted of 30 children selected using a purposive sampling technique and divided into an experimental class and a control class with 15 children each. Data collection was carried out through observation using instruments referring to the Test of Gross Motor Development-2 (TGMD-2). The experimental class participated in eight sessions of contemporary children's dance activities, while the control class participated in routine learning activities without special treatment. Data analysis was carried out using the Wilcoxon Signed-Rank Test through the assistance of IBM SPSS Statistics. The results showed that contemporary children's dance activities had a significant positive effect on children's gross motor skills. This was shown by an increase in posttest scores in the experimental class compared to the pretest results. Thus, contemporary children's dance activities can be used as effective learning activities to stimulate gross motor development in early childhood education.